Practical portfolio performance measurement and attribution - Bacon, Carl R. (Wiley finance, 2023)
"Performance measurement and attribution are key tools in informing investment decisions and strategies. Performance measurement is the quality control of the investment decision process, enabling money managers to calculate return, understand the behavior of a portfolio of assets, communicate with clients and determine how performance can be improved. The process of adding value via benchmarking, asset allocation, security analysis, portfolio construction, and executing transactions is collectively described as the investment decision process. There are many stakeholders in the investment decision process; this book focuses on the investors or owners of capital and the firms managing their assets (asset managers or individual portfolio managers)"--